Effect of Major Political Change on Stock Market Volatility in Nepal - Oli, Tilak; Pokhrel, Sandeep; Shrestha, Surakshya; Bhattarai, Sushil; Bista, Nar Bahadur (Nepalese Journal of Finance, 2025)
This study examines the effect of major political change on stock market volatility in Nepal. NEPSE index and market price per share are selected as the dependent variables. The selected independent variables are political events, political stability, consumer price index, broad money supply, control of corruption and regulatory quality. The study is based on secondary data of 15 Nepalese commercial banks with 150 observations for the period from 2014/15 to 2023/24. The data were collected from database maintained by World Bank, Nepal Rastra Bank, Ministry of Finance, NEPSE, SEBON and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of major political change on stock market volatility in Nepal. The study showed that consumer price index has a positive impact on NEPSE index and market price per share. It indicates that increase in consumer price index leads to increase in NEPSE index and market price per share. Similarly, political stability has a positive impact on NEPSE index and market price per share. It indicates that stable political environment leads to increase in NEPSE index and market price per share. Likewise, political events has a positive impact on NEPSE index and market price per share. It indicates that political events that support the government lead to increase in NEPSE index and market price per share. However, money supply has a negative impact on NEPSE index and market price per share. It indicates that increase in money supply leads to decrease in NEPSE index and market price per share. In contrast, control of corruption has a positive impact on NEPSE index and market price per share. It indicates that transparent and strong action taken by the government regarding corruption leads to increase in NEPSE index and market price per share. However, regulatory quality has a negative impact on NEPSE index and market price per share. It indicates that standard and transparent regulatory system leads to decrease in NEPSE index and market price per share.